Decentralized Finance: Bibliometric Analysis and Research Trends - Ma’arif, Syahrul; Maufiquddin, Fiqih; Dhevyantoa, Benny; Krisdiana, Krisdiana; Setiawan, Adi (Malikussaleh University, Aceh, Indonesia, 2025)
This research explores the developments and challenges in decentralized finance (DeFi) since 2015 and the increasing use of blockchain technology. DeFi provides access to financial services without traditional intermediaries, improving the economic system's efficiency through automated and transparent smart contracts. The bibliometric analysis shows a significant growth in DeFi-related publications, with 1,909 articles identified between 2015 and 2025. The research also highlights the importance of collaboration between authors and stakeholders to build a more secure and sustainable financial ecosystem. Analysis results using VOSviewer identified 173 keywords in 18 clusters, focusing on